UV IRRADIATION OF CARBONACEOUS METEORITES MAY SYNTHESIZE SMALL ORGANIC ACIDS ON MARS - Buckner, D. K.; Wilhelm, M. B.; Cooper, G.; Williams, A. J.; Schuerger, A. C.; Aponte, J. C.; Foustoukos, D.; Seguin, Frederic (AGU, 2025)
Organics are required for life as we know it and are ubiquitous to primitive abiotic exogenous materials, including carbonaceous chondrites [1,2]. Since biotic and abiotic synthesis mechanisms differ, organics bear molecular structures, distributions, and isotopic signatures that can indicate biological vs astrochemical/geological origin, making organics high-priority targets in astrobiological exploration of Mars [1]. Deconvolving the origin of Martian carbon is complex: multiple sources are expected, including exogenous delivery [2], abiotic in situ production [3], and potentially life [1]. Post depositional alteration via ionizing cosmic radiation and UV can complicate the signal [4]. Photochemical reactions can destroy, transform, or synthesize organics; radiolysis rates vary by molecule, functional group, and mineral associations [5]. Meteoritic organics are well-understood on Earth [2], but their evolution on Mars has not been constrained: characterizing UV alteration of exogenous organics is key to deconvolving the abiotic background for Mars life detection, especially compared to cosmic radiation, which alters organics differently [4,5]. Toward this goal, we exposed powdered Aguas Zarcas (AZ) meteorite and SiO2 blanks to Mars-like UV under analog conditions in the Planetary Atmospheres Chamber (PAC) [6] for ~100 sols equivalent.
American Geophysical Union (AGU25) New Orleans, LA, December 15-19, 2025